Anti Bacterial Activity of Fungi TIF-1 as Saponin Producer - Willy Tirza Eden; Ersanghono Kusumo; Eko Budi Susatyo; Kasmui Kasmui (Journal of Natural Sciences and Mathematics Research, 2016)
Treatment of microbial resistance is one of humankind's greatest challenges in terms of fight against infectious diseases. One way to overcome microbial resistance is discovery of potent new antimicrobial compounds against variety of microbial pathogens. Land is one potential source of microorganisms. This study aims to screen in order to get a fungal strains isolated from soil exposed to waste the pharmaceutical industry which possess antibacterial activity. Antibacterial activity test conducted on two types of bacteria, namely Staphylococcus aureus as Gram-positive bacteria and Escherichia coli as Gram-negative bacteria. The test results can be known isolates of fungi which has potential as an antibacterial, for then these are fermented for 10 days. Fermented then partitioned by using ethyl acetate. Initial screening showed that the fungi code TIF-1 as the most active fungi. Ethyl acetate soluble fraction was then identified the active compounds using thin layer chromatography method with various reagent spray. Bioautografi test results show that the saponins which play role in the antibacterial activity. ©2016 JNSMR UIN Walisongo. All rights reserved.